Dilemma of Hospital Nurses in Malang City: When Job Stress Triggers Turnover Intention, Can Burnout and Job Satisfaction Mediate? - Fathorrahman, Fathorrahman; Murtianingsih, Murtianingsih; Eka Putra, Hilman; Soares, Agusto da Conceicao (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
The persistent health problems in Indonesia have forced the government to act so that the public can still feel justice and obtain their rights. Since the government regulation regarding the tiered referral system was implemented, there has been an increase in referrals to D-type and C-type hospitals because of their position as the first-level referral facility in the BPJS health service program. In the healthcare industry, nurses play a crucial role as essential human resources in hospitals, responsible for monitoring patient health and providing care. However, hospitals continue to grapple with the serious issue of employees intending to leave their jobs. The data collection technique in this study was to use questionnaires distributed directly and randomly through Google Forms to 100 respondents from C-type hospital nurses in Malang City. The data collected was analyzed using Structural Equation Modeling (SEM-PLS). The research findings conclude that turnover intention is directly influenced by job stress, burnout, and job satisfaction, and that the job stress variable has a positive effect on burnout and job satisfaction. Additionally, Burnout and Job Satisfaction mediate the influence of Job Stress on turnover intention.